Behavior Healthy and Clean Life at Household (PHBS RT) In Sidorejo Village Brangsong District Of Kendal - Ahmad Sugeng Prayitno; S. Eko CH Purnomo; Hudiono Hudiono (UPPM Poltekkes Kemenkes Semarang, 2015)
This Research is including research of Explanatory research that is to connect free variable that is characteristic, mount knowledge, attitude, exploiting of service of information presentation and health about PHBS RT to family with with variable tied that is applied PHBS RT . Population in this research  entire/all family head in Sidorejo village with sampel counted 342 familly. Analysis the used  with analysis of univariat to depict various factor related to PHBS RT and of applied PHBS RT, and bivariate analysis to know relation between various factor influencing PHBS RT applied and of applied PHBS RT use test of rank Spearman.There is relation between family characteristic, knowledge of head family, attitude of head family, exploiting of medium service of information presentation and health of PHBS RT applied with PHBS RT